2017
DOI: 10.1177/0967010617709399
|View full text |Cite
|
Sign up to set email alerts
|

Seeing like a satellite: Remote sensing and the ontological politics of environmental security

Abstract: The article furthers the debate on environmental security by highlighting the role of visual technologies such as satellite remote sensing in the construction of threats and risks. It provides a rereading of the critical literature on environmental security through the lens of Actor-Network Theory and argues for understanding environmental security as a form of ontological politics. A theoretical framework around the notion of visual assemblage is developed that accounts for the hybrid, socio-technical charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…The persistence of the idea that climate change can cause violence reflects an ontology of social relations as inherently agonistic (Bregazzi and Jackson, 2018), which gives rise to epistemologies that ignore everything about those peopled relations in favour of mathematical abstractions in order to give scientific expression to this ontological position. It is a self-fulfilling science made possible by the multi-causal and complex nature of armed conflict, which remains a significant challenge to both theory and epistemology (Cederman and Weidmann, 2017; Bischel, 2017), and by the extensive use of visual technologies that encourage a panoptic view of the world as a stage whose changing nature is in turn assumed to change political behaviours (Barnett, 2009; Rothe, 2017). This ontological position is itself political, performing again and again a world where peace is an aberration and violence is a normal condition that must be accepted and for which we must prepare through the ability to meet violence with violence, which in turn provides the material and ideational preconditions that increase the risk of violence.…”
Section: The Implausible Geographies Of Climate Change and Armed Conflictmentioning
confidence: 99%
“…The persistence of the idea that climate change can cause violence reflects an ontology of social relations as inherently agonistic (Bregazzi and Jackson, 2018), which gives rise to epistemologies that ignore everything about those peopled relations in favour of mathematical abstractions in order to give scientific expression to this ontological position. It is a self-fulfilling science made possible by the multi-causal and complex nature of armed conflict, which remains a significant challenge to both theory and epistemology (Cederman and Weidmann, 2017; Bischel, 2017), and by the extensive use of visual technologies that encourage a panoptic view of the world as a stage whose changing nature is in turn assumed to change political behaviours (Barnett, 2009; Rothe, 2017). This ontological position is itself political, performing again and again a world where peace is an aberration and violence is a normal condition that must be accepted and for which we must prepare through the ability to meet violence with violence, which in turn provides the material and ideational preconditions that increase the risk of violence.…”
Section: The Implausible Geographies Of Climate Change and Armed Conflictmentioning
confidence: 99%
“…On their in-depth literature review about DT Hausberg et al, 2019 have found that big data is the research stream with most contributions and the artificial intelligence and machine learning are those technologies that have a significant presence. Moreover, among the several research streams identified by authors, one was named "society"; it consists of works that deal with the role of digital technologies in the following issues: Society and communication (Carolan, 2017;Gano, 2015;Madsen et al, 2016) Policy and international (Chandler, 2015;Rothe, 2017) Philosophy and ethics (Lake, 2017) Thus, this stream, particularly relevant for our study, is characterized by a multidisciplinary approach that takes into account the DT from a societal perspective, with a particular focus on not only the opportunities but also risks connected to the big data and digital technology adoption.…”
Section: Digital Transformationmentioning
confidence: 99%
“…Historically, the opening and commercialization of remote sensing technology in 1990s happened at the same time as a shift in environmental security discourse towards human security and resilience. The focus of environmental security in recent decades has increasingly shifted away from the international system or the nation-state towards individuals' and local communities' vulnerabilities and local environmental risks [114]. New actors, including non-government organizations, commercial entities, social scientists, and general public, are increasingly involved in forming narratives and storylines of environmental migration and conflict, because of the easy access to visual assemblages of EWM Big Data.…”
Section: Problems Big Data Can Tackle But With Some Helpmentioning
confidence: 99%
“…Currently EWM Big Data analytics address more association type of inference than causal inference; thus, Big Data alone is unlikely to provide explanations of causal mechanisms on the observed environment processes [114,116]. In other words, rather than providing answers to questions, the current Big Data platforms mainly enable the cability for researchers and policymakers to seek courses of action and to determine their consequences [117].…”
Section: Problems Big Data Can Eventually Solvementioning
confidence: 99%